2013
DOI: 10.1128/jvi.01158-12
|View full text |Cite
|
Sign up to set email alerts
|

The Herpes Simplex Virus 1 Us11 Protein Inhibits Autophagy through Its Interaction with the Protein Kinase PKR

Abstract: Autophagy is now known to be an essential component of host innate and adaptive immunity. Several herpesviruses have developed various strategies to evade this antiviral host defense. Herpes simplex virus 1 (HSV-1) blocks autophagy in fibroblasts and in neurons, and the ICP34.5 protein is important for the resistance of HSV-1 to autophagy because of its interaction with the autophagy machinery protein Beclin 1. ICP34.5 also counteracts the shutoff of protein synthesis mediated by the doublestranded RNA (dsRNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
151
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 56 publications
2
151
0
Order By: Relevance
“…Despite seemingly discrepant findings, it is plausible to speculate that an alternative mechanism other than xenophagic degradation might be involved in the immune control by autophagy, especially considering the well-accepted fact that HSV-1 suppresses cellular autophagy in a multitude of ways. 28,29,32,33 Other than the controversial xenophagic degradation, autophagic influence is observed in both major histocompatibility complex class I (MHC-I) and class II (MHC-II) antigen presentation pathways, which aids adaptive immune activation. 33,34 Infection with mutant HSV-1, which is defective in BECN1 binding and therefore in counteracting autophagy, stimulates a more robust HSV-1-specific CD4 C T cell response in vivo, as compared to its marker-rescued wild-type counterpart.…”
Section: Herpes Simplex Virus Type-1 Primary Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite seemingly discrepant findings, it is plausible to speculate that an alternative mechanism other than xenophagic degradation might be involved in the immune control by autophagy, especially considering the well-accepted fact that HSV-1 suppresses cellular autophagy in a multitude of ways. 28,29,32,33 Other than the controversial xenophagic degradation, autophagic influence is observed in both major histocompatibility complex class I (MHC-I) and class II (MHC-II) antigen presentation pathways, which aids adaptive immune activation. 33,34 Infection with mutant HSV-1, which is defective in BECN1 binding and therefore in counteracting autophagy, stimulates a more robust HSV-1-specific CD4 C T cell response in vivo, as compared to its marker-rescued wild-type counterpart.…”
Section: Herpes Simplex Virus Type-1 Primary Infectionmentioning
confidence: 99%
“…In addition to ICP34.5, tegument protein Us11 has also been implicated in the regulation of the autophagy pathway. 32 Us11 is an abundant viral protein produced in the late stage of the viral life cycle, which physically interacts with EIF2AK2 to prevent EIF2AK2-mediated phosphorylation of EIF2S1 (Fig. 1).…”
Section: Hsv-1 Inhibition Of Cellular Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 and HSV-2 are also capable of modulating autophagy, termed type II programmed cell death (Tallóczy et al 2001;Tallóczy et al 2006;McFarlane et al 2011;Lussignol et al 2013). Autophagy is an essential catabolic process that maintains cellular integrity by degrading cytoplasmic constituents and organelles (Deretic and Levine 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that at the early stage of infection HSV-1 provokes autophagy (McFarlane et al 2011). However, some viral proteins (ICP34.5 and US11) synthesized during the subsequent phases of productive infection function as powerful inhibitors of the autophagic process (Tallóczy et al 2001;Tallóczy et al 2006;Orvedahl et al 2007;Lussignol et al 2013). ICP34.5 of HSV-1 antagonizes autophagy by binding Beclin-1, and by blocking the double-stranded RNA-dependent protein kinase/eukaryotic translation initiation factor 2α (PKR/ eIF2α) pathway (Tallóczy et al 2006;Orvedahl et al 2007).…”
Section: Introductionmentioning
confidence: 99%